Taṭbīq Ṭarīqah Ĥalli al-Musykilāt litarqiyyah al-Fuđûl al-‘Ilmī wa Mahārāt al-Lugah al-‘Arabiyyah ladai Ṭalabah al-Madrasah - Musfida, Hanni’atul; Harisca, Rodhi; Sutarjo, J. (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research focuses on the application of problem solving-based learning methods and is designed to encourage students to actively participate in the learning process through solving real problems. A qualitative approach was used in the research design, as the study included 40 students as a full number for the research, and 20 of them were selected as a sample. Data were collected through interviews and observations with Arabic language teachers and students. The researchers used various data collection techniques to analyze scientific curiosity and develop students' Arabic language skills. Data were analyzed using qualitative methods to evaluate the effectiveness of the problem-solving method in improving students' skills and scientific curiosity. The research results show that problem solving-based learning methods significantly increase students' curiosity, which is demonstrated through their active participation in class and further exploration of the lesson material. Students' proficiency in Arabic has also increased, as can be seen from their ability to complete assignments and understand the concepts taught.